2013
DOI: 10.2106/jbjs.l.00903
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Carpal Tunnel Release at a Minimum of Ten Years

Abstract: At an average of thirteen years after open carpal tunnel release, the majority of patients are satisfied and free of symptoms of carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 26 publications
(27 reference statements)
4
51
1
1
Order By: Relevance
“…The score of one, being the minimum score, indicates they have no complaints and five, the maximum score, indicates high severity and functional loss. A score > 2 can be considered as poor [25]. We started with the BTCQ to inform and relax the patient and for temperature accommodation.…”
Section: Evaluation Of Symptoms and Functional Statusmentioning
confidence: 99%
“…The score of one, being the minimum score, indicates they have no complaints and five, the maximum score, indicates high severity and functional loss. A score > 2 can be considered as poor [25]. We started with the BTCQ to inform and relax the patient and for temperature accommodation.…”
Section: Evaluation Of Symptoms and Functional Statusmentioning
confidence: 99%
“…Muramatsu et al [ 13 ] achieved good or excellent results in 13 out of 15 RA patients treated with open release and synovectomy. Conversely, Louie et al [ 42 ] reported that patients with a carpal tunnel syndrome-confounding comorbidity, such as diabetes mellitus, polyneuropathy, rheumatoid arthritis, or osteoarthritis, had worse function and satisfaction after surgery as compared to those without a confounding morbidity at 10-year follow-up.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Less than two percent require revision carpal tunnel surgery. 24 Conventional open carpal tunnel release is usually performed under local anaesthetic with or without IV sedation. A tourniquet is used depending on surgeon preference.…”
Section: Current Opinion On Surgical Treatment For Ctsmentioning
confidence: 99%